Literature Review: Improving Lecturers Instructing Quality through Planning, Implementation, and Evaluation as HR Transformation for Indonesian Universities' Future - Abd. Rasyid Syamsuri; Payung Harahap; Julianto Hutasuhut; Abd. Halim (International Journal of Business, Technology and Organizational Behavior (IJBTOB), 2022)
The literature review in this article intends to address the theoretical needs in planning, implementing, and evaluating as the Transformation of Human Resources (HR) for the future of the university in order to improve the caliber of lecturers' teaching. Planning is necessary for effective teaching in order to keep instructors and college students on the same page. Applying the right technology raises the bar for curricular and instructional advice, development, and professional support at institutions. Implementing instruction is possible if lecturers and college students take an active part in the quality improvement process. In the interaction between teaching and learning that affects cognitive, constructivist, transformational, and behavioral theories in the university setting, lecturers play a significant role. The effectiveness of lecturers' instruction can also be assessed through training, research, and technology transfer. By providing information, instructional materials, and human resource development geared on developing college students' skills and capabilities, lecturers can enhance college students' talents and widen their horizons. In this perspective, education is viewed as a technological process and as a product that can be packaged and applied to assess the effectiveness of instruction. Big Data and the Internet of Things (IoT) are two examples of artificial intelligence technologies that could be the focus of future trends in the use of learning assistance software. This solution not only increases available space and learning opportunities for college students while also enhancing the quality of their education, but it also assists lecturers in utilizing digitization to their advantage in the future of higher education.